THE ANALYSIS OF HEADLINESE AND TOPIC VALUE OF HEADLINES NEWS IN DAILY ONLINE NEWSPAPER “THE JAKARTA POST” - Suryahadi, R Agus; Solo, Lenny (Dialectical Literature and Educational Journal, 2024)
This study investigates the use of Headlinese and the topic value of Headlines News in the daily online news publication "THE JAKARTA POST”. Headlinese refers to a style of writing commonly used in Headlines News, characterized by condensed phrases, abbreviations, and present tense verbs. The research aims to analyze the prevalence of Headlinese in Headlines News and identify the prominent topics covered by " THE JAKARTA POST " during the month of August 2023. The research methodology involves collecting Headlines News from " THE JAKARTA POST " archives for the specified time frame and conducting a word-by-word analysis to identify the stylistic features of Headlinese. Additionally, the study categorizes the Headlines News based on their topic value, including politics, economics, sports, arts, and other relevant themes. The findings reveal the frequency of occurrence of specific words and phrases across multiple editions of Headlines News, providing insights into the linguistic patterns and thematic trends in " THE JAKARTA POST”. The analysis also highlights the effectiveness of Headlinese in conveying information succinctly and capturing readers' attention. Based on the results, implications for English teachers, students, readers, and other researchers are discussed, along with suggestions for future studies in the field of Headlines News analysis and journalistic language.